Women in neurointervention, a gender gap? Results of a prospective online survey. Issue 3 (June 2022) - Power, Sarah; Biondi, Alessandra; Saatci, Isil; Bennett, Kathleen; Mahadevan, Jeyaledchumy; Januel, Anne Christine; Singhara Na Ayudhaya, Sirintara (Pongpech); Agid, Ronit
Background and Purpose: Women's representation in medicine has increased over time yet the proportion of women practicing neurointervention remains low. We conducted an anonymous online survey through which we could explore the gender gap in neurointervention, identify potential issues, difficulties, or obstacles women might face, and evaluate if men encounter similar issues. Methods: An online questionnaire was designed in SurveyMonkey®. Invitation to participate was emailed through national and international neurointerventional societies as well as directly through private mailing lists to men and women working in neurointervention. Responses were collected from 10 May 2019 to 10 September 2019. Results: There were 295 complete responses, 173 (59%) male and 122 (41%) female. Most respondents (83%) fell within age categories 35–60 years, with representation from 40 countries across five continents. In all 95% were working full time, 73% had worked as a neurointerventionalist for >6 years, 77% worked in University-affiliated teaching institutions. Almost half of the respondents indicated no female neurointerventionalist worked in their center. Female respondents were younger and age-adjusted analysis was undertaken. Significantly fewer females than males were married and had children. Significantly fewer females held supervisory roles, held academic titles, and significantly less had a mentor. Females were less satisfied in their careers. More females felt they receive less recognition than colleagues of the opposite sex. Males had a greater proportion of work time dedicated to neurointervention. Similar proportions of both genders experienced bullying in work (40%–47%); however, sexual harassment was more common for females. There were no differences between genders in how they dealt with complications or their effects on mental well-being. Conclusion: There are many potential reasons why women are underrepresented in neurointervention, however, the literature suggests this is not unique to our specialty. Multiple long-term strategies will be necessary to address these issues, some of which are discussed in the article.